2011
DOI: 10.1152/japplphysiol.00039.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activation by the cold pressor test does not increase the muscle force generation capacity

Abstract: A positive inotropic action by the sympathetic nervous system on skeletal muscles has been observed and investigated in animal and in vitro studies. This action provided a theoretical basis for the putative ergogenic action of catecholamines and adrenergic agonists, although there is no clear evidence of this effect in humans. The aim of this study was to investigate the occurrence of inotropic effects associated to physiological sympathetic activation in healthy subjects. The muscle force capacity was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…(4) includes three variables to characterize the average twitch profile and one to provide a better estimation in case of underdetermined systems. The twitch response was modeled using a modified version of the impulse response described by Fuglevand et al (Fuglevand et al, 1993) that has been proposed by Roatta and Farina (Roatta and Farina, 2011) in a previous study:…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…(4) includes three variables to characterize the average twitch profile and one to provide a better estimation in case of underdetermined systems. The twitch response was modeled using a modified version of the impulse response described by Fuglevand et al (Fuglevand et al, 1993) that has been proposed by Roatta and Farina (Roatta and Farina, 2011) in a previous study:…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…Motor unit activity during the exertion of muscle force was evaluated using surface electromyography (EMG) [ 14 , 15 ]. The surface EMG signals of the intermediate portion of the right vastus medialis were detected during leg extension strength measurement with the Ambu® Blue Sensor M (Ambu Ltd., Ballerup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, the adrenergic effects on skeletal muscles have been investigated during a physiological stress response in humans (Roatta et al 2008; Roatta & Farina, 2011). Interestingly, these studies showed weakening of selectively activated low‐threshold (thus presumably slow‐twitch) motor units during activation of the sympathetic nervous system by the cold pressor test (painful stimulus induced by immersion of one hand in icy water; Roatta et al 2008), in accordance with the positive lusitropic effect.…”
mentioning
confidence: 99%
“…Interestingly, these studies showed weakening of selectively activated low‐threshold (thus presumably slow‐twitch) motor units during activation of the sympathetic nervous system by the cold pressor test (painful stimulus induced by immersion of one hand in icy water; Roatta et al 2008), in accordance with the positive lusitropic effect. Further, it was not possible, using the same physiological stressor, to identify a positive inotropic effect when assessing all muscle fibres in the soleus and in the tibialis anterior muscles (Roatta & Farina, 2011). Of course, we cannot exclude that a stronger or different type of stress is necessary to produce a detectable enhancement of force.…”
mentioning
confidence: 99%